Balanço hídrico de microbacia com eucalipto e pastagem nativa na região da Campanha do RS. - Baumhardt, Edner (2010)
To obtain guidance in forestry hidrology it s inevitable to approach the understanding of the relations between the forest (natural or planted) and the water, concerning its use and consumption. However, the studies that elucidate the relation between water yield in a catchment under the effect of silviculture are, sometimes, divergent between each other. This points a challenge: what is the real effect of the Eucalyptus forest over the water balance in experimental catchments? Trying to answer this question, a historical controversy about the role made by the eucalyptos, concerning its hydrological function in the small watersheds in which they are cultivated, is debated by the present work. Then, it is intended to evaluate the influence of the vegetal coverage over the hydrological regime through the local water balance, using two experimental catchments, one of then forested MF, with the species of the gender Eucalyptus and the other with natural pastureland MC, both located in a characteristic zone of Pampa Biome. More specifically, it s intended to quantify some variable components of the water balance to estimate the water availability through the permanence curves of 40% to 100% at the time. The monitored variables are: precipitation and streamflow for both experimental catchments and evaluation of the interception in the forested catchments, to this manner, justify eventual differences as being proceeded of the kind of soil uses. In order to do this, it was instrumentalized two catchments in the characteristic zone of Pampa Biome. One, of natural pasture area with 21 ha, occupied by cattle breeding and another with silviculture of Eucalyptus with 92 ha, the latter with Permanent Preservation Area and Legal Reserve covering almost the half part of the area. The experimental area is located in the city of Rosário do Sul RS and it was monitored from October 2008 to September 2009. The precipitation incident registered in the MF was of 1297,6 mm and of 1434,1 mm in the MC. Concerning the rain interception by the forested area, it was concluded that with this methodology of planting, the interception was of 15% in the MF and 7,5% in the MC in relation to the incident precipitation. The months of January and February were identified as being that with the major drought. In these, the mensal permanence curves of the MF, considering the flows with permanence major than 40%, have presented a major quantity of water in relation to the natural pasture. Considering the annual curve, it was observed a major quantity of water for the flows with permanence major than 93% (Q93) in the MF. This can be explained by the major capacity of infiltration and regularization of the water courses in periods without rain. The water balance has showed that the use of the water by the MF has stated in 86% of the incident precipitation, while for the MC, this value was of 75%. Therefore, for the period of the research, the MF has showed itself more efficient in storage and water yield in drought periods than the MC, in spite of having a more elevated use of water.